2014
DOI: 10.1016/j.rse.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for chlorophyll fluorescence remote sensing from the Orbiting Carbon Observatory-2

Abstract: The Orbiting Carbon Observatory-2 (OCO-2), scheduled to launch in July 2014, is a NASA mission designed to measure atmospheric CO 2 . Its main purpose is to allow inversions of net flux estimates of CO 2 on regional to continental scales using the total column CO 2 retrieved using high-resolution spectra in the 0.76, 1.6, and 2.0 μm ranges. Recently, it was shown that solar-induced chlorophyll fluorescence (SIF), a proxy for gross primary production (GPP, carbon uptake through photosynthesis), can be accuratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
309
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 405 publications
(342 citation statements)
references
References 45 publications
7
309
0
Order By: Relevance
“…This finding indicates that SIF data can help us improve our current models of the global carbon cycle, which we have shown to substantially underestimate GPP in some large agricultural regions such as the US CB and the Indo-Gangetic Plain. The launch of the Orbiting Carbon Observatory-2 and the Sentinel 5-Precursor satellite missions in 2014 or 2015 will enormously improve the observational potential for SIF, up to a 100-fold increase in spatiotemporal resolution (42,43). This will especially benefit measurements over the typically fragmented agricultural areas, which suggests that SIF-based estimates of crop photosynthesis will soon become a unique data set for both an unbiased monitoring of agricultural productivity and the benchmarking of carbon cycle models.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicates that SIF data can help us improve our current models of the global carbon cycle, which we have shown to substantially underestimate GPP in some large agricultural regions such as the US CB and the Indo-Gangetic Plain. The launch of the Orbiting Carbon Observatory-2 and the Sentinel 5-Precursor satellite missions in 2014 or 2015 will enormously improve the observational potential for SIF, up to a 100-fold increase in spatiotemporal resolution (42,43). This will especially benefit measurements over the typically fragmented agricultural areas, which suggests that SIF-based estimates of crop photosynthesis will soon become a unique data set for both an unbiased monitoring of agricultural productivity and the benchmarking of carbon cycle models.…”
Section: Resultsmentioning
confidence: 99%
“…Dry to wet transitional regions are correctly characterized, such as in Portugal‐Spain, North Africa, the Sahel, the east‐west gradient in the continental United States, and in India. Deserts are also correctly characterized with the lowest RSIF values, whereas the original SIF data tend to be noisy over deserts and more erratic due to the inherent noise in the small‐amplitude SIF data (Frankenberg et al, 2014; Joiner et al, 2011; Köhler et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, a new retrieval of red SIF from GOME‐2 instrument was developed (Joiner et al, 2016), which is noisy but could yield important additional information on LUE. New fluorescence observations at higher spatial and temporal resolution and with higher signal‐to‐noise ratio, such as from OCO‐2 (Frankenberg et al, 2014; Li et al, 2017; Schimel et al, 2015), Florescence Explorer (FLEX) (Kraft et al, 2012), TROPOspheric Monitoring Instrument (TROPOMI) (Guanter et al, 2015), or Geostationary Carbon Cycle Observatory (GeoCARB) (O'Brien et al, 2016), might help better retrieve changes in LUE, maybe in combination with this RSIF product. In addition, SIF observations at other spectral frequencies and at higher temporal resolution (diurnal) might yield critical information regarding variations in SIF yield and LUE.…”
Section: Discussionmentioning
confidence: 99%
“…The GOME-2 spatial footprint (i.e., support) of the observations is 40 km × 80 km (Joiner et al, 2013), and the volume of available data is approximately 2 × 10 5 SIF observations per week. Multiple recent studies have demonstrated the potential use of satellite observations of SIF for understanding the photosynthetic CO 2 uptake at large scales (Joiner et al, 2011(Joiner et al, , 2012(Joiner et al, , 2013Frankenberg et al, 2011Frankenberg et al, , 2012Frankenberg et al, , 2014Guanter et al, 2012;Lee et al, 2013). Satellite SIF measurements can be used with land surface models to understand gross primary production (GPP) response to environmental stress (e.g., Lee et al, 2013) and to improve the representation of GPP.…”
Section: Global Land Solar-induced Fluorescence Fieldsmentioning
confidence: 99%